Productivity of semi-domesticated reindeer in Finland - Kojola, Ilpo; Helle, Timo; Aikio, Pekka (Rangifer, 1991)
In spite of a twofold increase in the density of reindeer in Finland from 1974 to 1987, meat production per reindeer increased during this period. This was possible due to calf harvesting and supplemental feeding. Results from multiple regression models indicated that calf harvesting influenced both per unit area and per capita production more than supplemental feeding. Correlation between meat production and animal density decreased with increased supplemental feeding. Traditionally, southern and central herds of reindeer fed mainly on arboreal lichens in late winter; however, due to large-scale logging, woodlands rich of arboreal lichens had been greatly reduced. Economic carrying capacity of the winter range apparently has been exceeded in the south; a heavy crash in the number of reindeer is likely if supplemental feeding ceases. In northern herds, intensive calf harvesting enabled satisfactory yield without supplemental feeding. In northern herds, yield increased mainly per unit area (i.e. by increases in herd size); in the south yield per reindeer increased. Lithantuotantoon vaikuttavat tekijat Suomen poron-hoidossa. Abstract in Finnish / Tiivistelmd: Huolimatta Suomessa vuosien 1974 ja 1987 valilla tapahtuneesta porotiheyden kaksinkertaistumisesta, lihantuotto poroa kohti kasvoi jakson aikana. Tama johtui oletettavasti vasateurastuksesta ja lisaruokinnasta. Monimu-uttujaregressiomallien tulosten perusteella vasateurastuksella nayttaisi olevan lisaruokintaa suurempi vaikutus seka poroa etta pinta-alaa kohti laskettuun tuottoon. Ruokinnan tehostuessa pienentyi lihantuoton ja porotiheyden valinen riippuvuus. Etelaosan ja keskiosan porot syovat perinteisesti puussa kasvavia jakalia kevattalvella. Hakkuista johtuen luppometsien osuus on suuresti vahentynyt. Talvilaidunten ekonomien kantokyky on ilmeisesti ylitetty etela- ja keski-osassa; syva romahdus poromaarissa on todennakoista, jos ruokinta lopetettaisiin. Pohjoisosassa voima-perainen vasate-urastus mahdollistaa tyydyttavan tuoton ilman ruokintaa. Pohjoisessa tuotto kasvoi pinta-alayksikkoa kohden (poro-maarat kasvoivat), etelassa kasvoi poroa kohti laskettu tuotto.